Differences in life expectancy with and without disease using reported, measured, and combined estimates for hypertension and diabetes among older adults in Colombia - Margarita Osuna; Liliana Ruvalcaba; Eileen Crimmins; Carlos Cano; Jennifer Ailshire (PLoS ONE, 2026)
Background In Colombia, estimates of diabetes and hypertension prevalence differ substantially depending on the source of measurement. These differences have important implications for understanding disease burden in later life, particularly as the population ages and chronic conditions become more prevalent. Methods This study uses nationally representative data from SABE-Colombia 2015 to estimate the prevalence and diseased life expectancy (DLE) with diabetes and hypertension among adults 60 and older. Prevalence was calculated using three measures: reported diagnosis, measured high-risk and a combined estimate that includes both indicators. We further disaggregated each disease into three categories: controlled, uncontrolled, and unaware. DLE was estimated using the Sullivan method. Results For diabetes prevalence, the widest range between measures among men was at ages 80–84: 22.5% combined, 21.5% reported, and 6.7% measured. Among women the widest range occurred at ages 75–79: 34.4% combined, 32.0% reported, and 13.4% measured. An average man at age 60 was expected to live 3.8 years with diabetes using the combined measure, 3.5 years using reported diagnosis, and 1.5 years using measured data. An average women, at age 60,  had a DLE with diabetes of 5.0 years using the combined measure, 4.6 years using reported measure, and 2.0 years using measured data. For hypertension prevalence, the widest range between measures among men occurred at ages 65–69: 64.8% combined, 47.3% reported, and 32.6% measured. Among women, the widest range also occurred at ages 65–69: 74.0% combined, 63.6% reported, and 28.2% measured. At age 60, men were expected to live 13.9 years with hypertension using the combined measure, compared with 10.5 years using reported diagnosis and 8.3 years using measured data. For women, DLEat age 60 was 16.7 years combined, 14.4 years reported, and 8.0 years measured. Conclusion We found relatively high diabetes awareness and treatment. In contrast, for hypertension, reported diagnosis underestimated both prevalence and DLE compared to combined measures.